DIMENSI SUFISME DALAM RUMAH TANGGA PERSPEKTIF AL-GHAZALI - Ulum, Bahrul (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
Marriage is a sacred event where a husband and wife must have a strong bond in living it. A good attitude can be realized from various drives, including internal factors, what is meant is morality, attitude and action. The purpose of this study is to find out about the dimensions of Sufism in the household from Al-Ghazali's perspective, the factors that cause harmony and destruction of the household, the benefits of marriage and household etiquette. This study uses a qualitative research method with analysis used descriptive, with data collection techniques, examines theory through discussion and comparison of data with other references relevant to the discussion. The results of this study indicate that: 1). al-Ghazali's view is to try to improve morality by following the procedures of the Shari'a and imitating the footsteps exemplified by the Prophet Muhammad as an essential mirror of Shari'a. 2) There are 19 types of women to be avoided in the category of potential partners. 3). The criterion of a woman is her halal status and kindness. 4) The benefits of marriage include: children, suppressing lust, resting lust by making out with his wife and focusing his heart on managing the household. 5) marital problems include: negligence in seeking halal sustenance, not understanding the character of the spouse and lack of a sense of responsibility. 6) The solution to household harmony: remind each other of worship, give thanks and pray to Allah